PELATIHAN PEMBELAJARAN ANAK USIA DINI DALAM KEGAIATAN BELAJAR DARI RUMAH MASA PANDEMIK COVID-19 PADA WALI MURID di TK Al- HIDAYAH SIRENJA KABUPATEN DONGGALA - Andi Agusniatih; I Putu Suwika; Fitriana Fitriana (LP2M STP Mataram, 2022)
The problem that occurs is the obstacles for parents in carrying out learning from home (BDR) activities without being provided with appropriate learning knowledge for early childhood according to the stages of child development. Thus, there is a need for early childhood learning training and guidance as an alternative for early childhood that is appropriate for child development. The purpose of this service is to provide knowledge and be able to carry out good practices in assisting children or substitute teachers at home. There are three stages of this activity, namely: 1) the preparation stage; 2) Implementation of Activities; 3) Post Training. Evaluation Report. The results of service activities based on an evaluation questionnaire of the implementation of activities involving 20 parents showed that in early childhood learning for parents in the aspect of understanding children's learning there were 16 people in the good category and in the aspect of the ability to make educational games 13 people out of 20 guardians. it can be concluded that service activities can provide knowledge to the guardians of students to carry out good practices in assisting learning from home.